Performance Comparison Analysis of the Elias Delta Code Algorithm with the Even Rodeh Code Algorithm for Compressing Image Files - Elvia Hariska; Ega Yuliani; Surya Darma Nasution (The IJICS (International Journal of Informatics and Computer Science), 2021)
A file or files have a large size, especially an image file. So that it can affect a storage memory and also mess in the speed of data transmission. If an image file has a large capacity it can affect the sending process. So that the sending process has two possibilities, namely the image file sent will require a long process or the image file will experience failure in sending because the storage size exceeds the maximum limit. This problem can be overcome by compressing the data. Data compression can reduce the size of data storage on both internal and external memory, speeding up data transmission due to smaller storage sizes. Data compression has several algorithms that can be used. In this research, the writer will compare the performance of Elias Delta Code algorithm with even Rodeh Code algorithm. Thus obtaining which algorithm is the most efficient used for the image file compression process.